Primary Carcinoma in Squamous Cells of the Gallbladder - Javier Martínez Navarro; Virgen Yazmín Martínez Navarro; Lisanka Fumero Roldán (Revista Finlay)
Cancer in the gallbladder is infrequent. Its prognosis is related to the early detection and the degree of its penetration in the bladder wall. This carcinoma presents a high mortality therefore early diagnosis in a vital need. A case of an 81 year old patient is presented, with antecedents of type II diabetes mellitus and high blood pressure on permanent drug treatment. The patient was admitted to the internal medicine ward due to an increase of abdominal volume and generalized icterus, accompanied by a mild pain over the right hypochondria which appeared immediately after eating and relived with common analgesics. During the last month it was accompanied by a few vomits, marked asthenia, loss of appetite, intense and permanent dyspnea, and productive cough with yellowish expectoration and a moderate ascites. The severity of the illness did not allow finishing the case study. Clinical necropsy confirmed a diagnosis of primary gallbladder squamous cell carcinoma. This medical condition is an odd in our context reason for which the case is presented.